1988
DOI: 10.1055/s-0038-1647511
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Human Platelets by Acidic Mucopolysaccharide Extracted from Stichopus japonicus Selenka

Abstract: SummaryThe acidic mucopolysaccharide extracted from sea cucumber (Stichopus japonicus Selenka) (SJAMP) has been shown to cause platelets to aggregate. Using citrated platelet-rich plasma (PRP), washed platelets and formaldehyde-fixed platelets from humans, we investigated the effects of platelet inhibitors and various plasmas and their fractions on SJAMP-induced platelet aggregation. It was found that the lowest concentration of SJAMP required for the aggregation of human platelets was about 0.4 μg/ ml and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Compared with OSCS and AjFG, Fr-1–Fr-4 exhibited no FXII activation within the experimental concentration range (Figure 3C). Previous studies have shown that the native AjFG induces clumping of human, rat, rabbit, and mouse platelets, and causes a dramatic decrease in the platelet count [31,32]. In our present study, compared with ADP, Fr-1–Fr-4 did not exhibit platelet aggregation ( P > 0.05) (Figure S9).…”
Section: Resultssupporting
confidence: 51%
“…Compared with OSCS and AjFG, Fr-1–Fr-4 exhibited no FXII activation within the experimental concentration range (Figure 3C). Previous studies have shown that the native AjFG induces clumping of human, rat, rabbit, and mouse platelets, and causes a dramatic decrease in the platelet count [31,32]. In our present study, compared with ADP, Fr-1–Fr-4 did not exhibit platelet aggregation ( P > 0.05) (Figure S9).…”
Section: Resultssupporting
confidence: 51%
“…The observation that with decreasing fCS polymer size, elastase inhibition activity is retained, but that anticoagulant activity is much reduced, could be of value in some therapeutic applications where anti-inflammatory effects are desirable but where anticoagulant activity would be unwanted. It could also reduce the adverse effects associated with the use of long, highly sulfated polysaccharide chains ( 74 ) as demonstrated in LMWH ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…It contains more than 50 kinds of nutrients including amino acids, essential or polyunsaturated fatty acids, vitamins and trace elements, etc., and active substances, such as collagen proteins, polysaccharides, saponins and brain glycosides (Jiang et al, 2004). These substances have many roles of antitumor (Jin et al, 2009;Sugawara et al, 2006), anticoagulant (Li and Lian, 1988), lowering blood-fat (Liu et al, 2012), antifungal activity (Chludil et al, 2002;Kumar et al, 2007), inhibition of angiogenesis (Zhao et al, 2011), immunomodulatory , inducing neurite outgrowth (Kaneko et al, 2007). environment would be reduced and considerable economic benefits could be obtained.…”
Section: Introductionmentioning
confidence: 99%